Reduction of Effects of Dietary Aflatoxin B1 on Biochemical Parameters of the Fish Clarias Batrachus by Vitamin C: Life Sciences-Toxicology - Fatmi, Amjad; Ruby, Durreshahwar (International Journal of Life Science and Pharma Research, 2021)
Aflatoxins are produced mainly by molds Aspergillus flavus and Aspergillus parasiticus. They cause toxicity called aflatoxicosis in animals and human beings which is of great concern in aquaculture also. Aflatoxin B1 is the most potent of all the known aflatoxins which mediates its effects by producing reactive oxygen species (ROS) and by irreversible damage to DNA and proteins leading to genotoxicity and cytotoxicity. Vitamin C is a potent antioxidant and reduces reactivity of ROS by donating electrons to them. Previous investigations suggest its role in alleviating aflatoxicosis in Nile tilapia. Present studies were conducted to determine the reduction in the negative effects of aflatoxin B1 on blood biochemical parameters and liver glycogen of fish Clarias batrachus by dietary supplementation of vitamin C. In the present investigation 60 fish were divided into four groups. Each group comprised fifteen fish. Four types of feed were prepared on the basis of presence of aflatoxin B1 and vitamin C. Feed I consists of a basal diet given to the first group of fish or control. Feed II consisted of aflatoxin B1 contaminated feed given to second group of fish. In feed III and IV 300 mg/kg and 600 mg/kg vitamin C was added to aflatoxin B1 contaminated feed The objective of the present investigation was to explore the role of Vitamin C in reduction of adverse effects of aflatoxin on plasma biochemical parameters and liver glycogen of the fish Clarias batrachus. The group of fish that was given the feed II showed a significant increase in serum level of ALT, AST, bilirubin, blood urea, glucose and albumin globulin ratio but significant decrease was observed in total serum proteins and liver glycogen as a result of dietary aflatoxin .Supplementation of Vitamin C in the feed significantly decreased the adverse effects of aflatoxin and the parameters showed significant improvement. The group of fish fed with 600 mg/kg vitamin C showed best results and were nearly similar to those of the control. The present investigation revealed that feed containing 600 mg/kg vitamin C diminishes the effect of aflatoxin B1 in the fish reducing the health risk in humans consuming the fish as aflatoxins has the potential to accumulate and stay in the tissues of animals for long period of time.